Currency Convertibility and the Fund : Review and Prognosis - Galbis, Vicente (IMF Working Papers; Working Paper ;, 1996)
This paper reviews experience with currency convertibility on both the current and capital accounts, with particular attention to the Fund's concepts and policy implications. After discussing the basic concepts of convertibility, the paper reviews the experience with convertibility in three groups of Fund members--industrial countries, developing countries, and transition countries. The paper also discusses some policy options designed to encourage acceptance of convertibility by Fund members that have not yet done so.